Benefits, barriers and facilitators to golf participation among disabled people: identifying opportunities to increase uptake and foster inclusion - Monforte, J.; Smith, B.; Bennett, T. (International Journal of Golf Science, 2022)
Golf can have a positive impact upon physical and psychosocial health. However, it is not widely promoted to and for disabled people. In response, this review explores the benefits, barriers, and facilitators to golf participation among this population. 18 empirical studies, research reports, or other forms of grey literature documenting golf in relation to health for disabled people were identified. The results suggest that golf can yield a variety of health benefits for disabled people, of which we need stronger evidence. Sometimes, personal, social, and environmental barriers might prevent them to obtain such benefits. These include lack of adequate services, accessibility issues, classism, and ableism. Little evidence was found regarding facilitators. However, social interactions as well as free courses and equipment appear crucial to support regular participation. Despite evidence limitations, multiple recommendations are compiled that might be useful to orient future practice and policymaking. Overall, the article provides a modest but accessible resource to help transforming golf into a more inclusive and pleasurable activity for disabled people.